Which Contributes to Meniscal Repair, the Synovium or the Meniscus? An In Vivo Rabbit Model Study With the Freeze-Thaw Method. Issue 6 (May 2020) - Kim, WooYoung; Onodera, Tomohiro; Kondo, Eiji; Terkawi, Mohamad Alaa; Homan, Kentaro; Hishimura, Ryosuke; Iwasaki, Norimasa
Background: During meniscal tissue repair, the origin of the reparative cells of damaged meniscal tissue remains unclear. Hypothesis: Comparison of the influence between meniscal and synovial tissues on meniscal repair by the in vivo freeze-thaw method would clarify the origin of meniscal reparative cells. Study Design: Controlled laboratory study. Methods: A total of 48 mature Japanese white rabbits were divided into 4 groups according to the tissue (meniscal or synovial) that received freeze-thaw treatment. The meniscus of each group had a 2 mm–diameter cylindrical defect filled with alginate gel. Macroscopic and histologic evaluations of the reparative tissues were performed at 1, 3, and 6 weeks postoperatively. Additional postoperative measurements included cell density, which was the number of meniscal cells in the cut area per cut area (mm 2 ) of meniscus; cell density ratio, which was the cell density of the sample from each group per the average cell density of the intact meniscus; and cell death rate, which was the number of cells stained by propidium iodide per the number of cells stained by Hoechst 33342 of the meniscal tissue adjacent to the defect. Results: The macroscopic and histologic evaluations of the non–synovium freeze-thaw groups were significantly superior to those of the synovium freeze-thaw groups at 3 and 6 weeks postoperatively. Additionally, the meniscal cell density ratio and cell death rate in the freeze-thaw groups were significantly lower than those in the non–meniscal freeze-thaw groups at 3 and 6 weeks postoperatively. Conclusion: The freeze-thawed meniscus recovered few cells in its tissue even after 6 weeks. However, the defect was filled with fibrochondrocytes and proteoglycan when the synovium was intact. On the basis of these results, it is concluded that synovial cells are the primary contributors to meniscal injury repair. Clinical Relevance: In meniscal tissue engineering, there is no consensus on the best cell source for meniscal repair. Based on this study, increasing the synovial activity and contribution should be the main objective of meniscal tissue engineering. This study can establish the foundation for future meniscal tissue engineering.